Spirulina platensis in Japanese quail feeding alters fatty acid profiles and improves egg quality: Benefits to consumers - Dilkin J.D.* (2019)
© 2019 Wiley Periodicals, Inc.The aim of this study was to investigate whether microalgae in Japanese quail feed alters performance, fatty acid profiles in the eggs and egg quality. One hundred quails were distributed in four groups and five replicates of five birds per experimental group. The treatments consisted of four levels of Spirulina platensis microalgae (0%, 5%, 10%, and 15%) in the diets. We evaluated the productive performance and chemical-physical characteristics of eggs, the oxidant/antioxidant status in egg yolks, and the fatty acid profile in the diet and egg yolks. Microalgae in the diet did not influence egg production; however, it increased the yolk index as well as the color intensity of the yolk. Saturated and polyunsaturated fatty acid levels decreased in egg yolks, and monounsaturated fatty acid levels increased in the yolks. Lipid peroxidation levels were lower and total antioxidant capacity was higher in egg yolks of quails receiving microalgae in the diet. Practical applications: Microalgae in quail diets improves egg quality and provides benefits to consumer health, acting as an antioxidant and immune-stimulant. Microalgae in quail diets had positive effects on egg quality. This is because it reduced levels of saturated fatty acids that are undesirable, and increased monounsaturated fatty acid levels that are beneficial to the health of consumers. Finally, antioxidants increased in egg yolks, consequently reducing lipid peroxidation.